(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The use of motor vehicles has been strongly linked to rising levels of air pollution in rural areas as well as all over the world. These motor vehicles also produce huge amounts of carbon monoxide (CO), hydrocarbons (HC), nitrogen oxide (NOx), suspended particulate matter (SPM), and other air pollutants into the atmosphere. In the present investigation, the study area was Loni, located in Ahmednagar, and M.S. was selected and investigated for leaf area, length, width, and chlorophyll pigment, i.e., Chl a, Chl b, and carotenoids and xanthophylls. It was interesting to notice that in the control, the leaf region was bigger (31.18 cm2) when contrasted with the leaf region of the dirtied test (18.97cm2).The length of the dirty test was 11.49 cm,